A Survey of Critical Success Factors in the Malaysia e-Banking: A Perspective of UUM Postgraduate Students - Mohamad Ghazali, Norliza (2011)
The topic of this paper is: A survey of critical success factors in Malaysia e-Banking: An organizational perspective from the view of UUM postgraduate students. The main purpose of this study is to obtain the critical success factors from the organizational perspective in e-banking sectors in Malaysia from the perspective of ULTM Postgraduate students in UUMKL Campus. This study was conducted among 150 postgraduates of UUMKL by using questionnaires. The findings show that in Malaysia, technical capability of the e-banking systems is the critical success factors. Secure website and other related systems and IS integration are the technical capability of the e-banking success in Malaysia as compared to strategic factors. The results indicated that availability of resources and flexible organizational are the least important consideration to be the critical success factors in Malaysia.